2009
DOI: 10.4039/n08-069
|View full text |Cite
|
Sign up to set email alerts
|

Lymantria dispar sex pheromone is a behavioral antagonist to pheromonal attraction of male Lymantria mathura

Abstract: In a trapping study conducted in the experimental research forest of the Tohoku Research Center, Morioka, Honshu, Japan, we investigated the effect of heterospecific pheromone on pheromonal attraction of male Japanese gypsy moth, Lymantria disparjaponica (Motschulsky), and male pink gypsy moth, L. mathura Moore (Lepidoptera: Noctuidae: Lymantriinae). Traps baited with synthetic pheromone of L. d. japonica ((7R,8S)-cis-7,8-epoxy-2-methyloctadecane = (+)-disparlure (100 µg)) or L. mathura ((9R,10S,3Z,6Z)-cis-9,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…But these four chemicals had different binding affinity with PBPs, and PBP genes did not map to a quantitative trait locus for response to pheromone 37 . And therefore we can not classify them as agonists or antagonists of pheromone 38 , 39 , like (+)-D being a behavioral antagonists to pheromonal attraction of male L. mathura 40 . However, the different affinity of PBPs to chemicals showed that PBPs can recognize and decode the chemicals, and these chemicals did influence the behavior, but such result need to be confirmed in field experiments.…”
Section: Discussionmentioning
confidence: 99%
“…But these four chemicals had different binding affinity with PBPs, and PBP genes did not map to a quantitative trait locus for response to pheromone 37 . And therefore we can not classify them as agonists or antagonists of pheromone 38 , 39 , like (+)-D being a behavioral antagonists to pheromonal attraction of male L. mathura 40 . However, the different affinity of PBPs to chemicals showed that PBPs can recognize and decode the chemicals, and these chemicals did influence the behavior, but such result need to be confirmed in field experiments.…”
Section: Discussionmentioning
confidence: 99%
“…That the L. mathura pheromone components (+)and (-)-mathuralure, singly (Fig. 2) and in combination (Gries et al 2009), had no antagonistic effect on L. d. japonica is not understood because (+)-disparlure, in turn, is a behavioural antagonist to pheromonal communication by L. mathura (Gries et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…For efficient pheromone-based detection surveys of exotic species of Lymantria Hübner, lures for several species should be deployed. There is evidence, however, that components of the pheromone/volatile blend from one species can be antagonistic to that of another (Grant et al 1996;Gries et al 1996Gries et al , 2009. Thus, for optimal attractiveness, synthetic pheromone lures used in detection surveys require sufficient spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Our electrophysiological results alongside with the studies mentioned above on other species of tineids/sesiids suggest that the E 3 Z 13‐18:OH may be a putative pheromone antagonist. Closely related moth species, as well as phylogenetically distant species with completely different pheromone components can be antagonized by pheromone components from other lepidopterans living in the same habitat (Gries et al, 2009; Mozūraitis et al, 2006; Wang, Shen, et al, 2022). Pheromone antagonists have the great potential as an alternative material in integrated pest management strategies (Renou & Guerrero, 2000).…”
Section: Discussionmentioning
confidence: 99%